Interactional Effect of the Influential Parameters on Seismic Behaviour of the Concrete Surface Tanks - Alirezar Hassanpour Yasaghi; Mazhar Fatahi; Seyed Mehdi Seyed Alizadeh (Shock and Vibration)
Given to the importance of the tanks and their various applications in different industries, studying the seismic behaviour of these facilities is essential. In such structures, obtaining exact theoretical solution for the seismic behaviour of the tanks is very difficult due to the existence of the soil-structure interaction. In this study, seismic behaviour studying has been taken into account and in addition to considering three-dimensional model of finite element model of a surface rectangular tank and its beneath soil given to SSI and FSI effect, we have done required analysis and Drucker–Prager nonlinear model has been used to investigating more exactly to describe soil behaviour. Euler–Lagrange view with optional mesh displacement has been used for modelling tank-water interaction. According to the obtained results from this modelling, soil beneath the tank and soil-structure interaction affect highly on seismic behaviour of the surface tanks. Meanwhile, the response of the structure to the density changes and soil modulus of elasticity is more sensitive and changes in the coefficient of friction coefficient between the foundation surface and the soil and the internal friction angle do not have tangible effect on the response. The results reveal that the liquid containers response is more sensitive to the changes of the density and the soil modulus of elasticity more than friction coefficient between the surfaces and foundation and internal angle friction.